A modified formula of thermal focal length for lamp pumping Cr, Er:YSGG crystal with high performance 2.79 μm laser. (July 2019) - Fang, Zhongqing; Sun, Dunlu; Luo, Jianqiao; Zhang, Huili; Zhao, Xuyao; Quan, Cong; Hu, Lunzhen; Chen, Xiaolin; Cheng, Maojie; Zhang, Qingli; Yin, Shaotang
Highlights: Four Cr, Er:YSGG crystal were processed with the size of Ø 3–6 mm × 105 mm. A maximum pulse energy 1261 mJ operated at 5 Hz and 2.79 μm. The formula of the thermal focal length is modified further. Simulation results of the thermal focal lengths consist with the experiments well. Abstract: We demonstrate the laser and thermal properties on the four Cr, Er:YSGG crystal rods with different diameters from 3 to 6 mm. A maximum pulse energy 1261 mJ operated at 5 Hz and 2.79 μm is obtained on the rod of 4 mm diameter, corresponding to electrical-to-optical efficiency of 1.53% and slope efficiency 1.82%, respectively. Combining with the electrical-to-optical efficiency and thermal distribution, the formula of the thermal focal length is modified further. The simulation results of the thermal focal length for four crystals with different diameters are in good consistence with the measurement values, suggesting the revised formula is accurate and effective to calculate the thermal focal length.